One giant leap towards Australian adolescents'' understanding of the human papillomavirus vaccine. (March 2012) - Cooper Robbins, Spring; Skinner, S Rachel
Human papillomavirus (HPV) vaccination is becoming routine in many countries, and Australia has achieved high levels of uptake by implementing a school-based program. School-based delivery of the vaccine to adolescents is highly efficient, when compared with general practitioner or private provider delivery of vaccine to a population, in the absence of legislative mandates. However, challenges exist in implementing a complex health promotion initiative in the school setting. As we demonstrate in this article, knowledge and understanding of HPV and the HPV vaccine is very low among vaccinated and unvaccinated adolescents alike in Australia, and efforts to address this gap are only just beginning. This article explores some of the data on Australian young people''s knowledge and attitudes towards HPV vaccination, as well as some of the implications and possible changes that could be implemented in routine provision of HPV vaccination, both in Australia and internationally.